Інтер'єр будівель небелівської локальної групи трипільської культури - Черновол, Д.К. (Археологія, 2012)
Охарактеризовано деталі облаштування жител небелівської групи пам’яток трипільської культури та інтер’єр першого й другого поверхів. В каждой локальной группе трипольской культуры интерьер жилищ имеет определенные особенности. В статье рассмотрены постройки небелевской группы. Она выделена С.Н. Рыжовым и относится к памятникам западнотрипольской культуры этапа В/II Буго-Днепровского междуречья. Первые раскопки небелевских поселений были проведены в конце 19 в. Ныне исследована 21 постройка. Dwellings interior has its certain peculiarities in each local group of Trypillya culture. Buildings of Nebelivka group are analyzed in the article. This group was determined by S.M. Ryzhov and it belongs to the Western Trypillya culture monuments of the B II stage in the region between the Buh and Dnipro Rivers. First excavations at Nebelivka group settlements were conducted in the end of the 19th c. Today 21 structures are studied.